PENGARUH AUDIT OPINION, AUDIT TENURE, DAN PROFITABILITAS TERHADAP AUDIT DELAY DENGAN REPUTASI KANTOR AKUNTAN PUBLIK(KAP) SEBAGAI VARIABEL MODERASI - SHANIA ARIESTIA; Tanggor Sihombing (Jurakunman (Jurnal Akuntansi dan Manajemen), 2021)
The aim of this study is to find out how the effect of audit opinion, audit tenure, and profitability on audit delay with the public accounting firm reputation as a moderating variable. The sample of this study is a manufacturing company from the basic industry and chemical sectors listed on S&P Global during the 2017-2019 period, with a final sample size of 225 samples. The data analysis method used is a multiple linear regression model using STATA software by testing two research models, namely model 1 (model without moderating variables) and model 2 (model with moderating variables). According to the results of the model 1 hypothesis test that has been carried out, it shows that audit opinion has an effect on audit delay, while audit tenure and profitability do not have a significant effect on audit delay. Meanwhile, the results of the model 2 hypothesis test show that the public accounting firm reputation able to moderate the relationship between audit opinion and audit delay, while the public accounting firm reputation is unable to moderate the relationship between audit tenure and profitability. Keywords: Audit Delay, Audit Tenure, Public Accounting Firm Reputation, Profitability